The influence of technological teaching materials in the learning process of english language in students of second year of bachillerato - Montesdeoca Delgado, Eizer Fabián (Machala : Universidad Técnica de Machala, 2016)
Teaching learning materials applied must be the first goal of every single development by the teachers in their classes, as well as the learning influences should be done in it. this project goes to the teachers, especially for those ones who are responsible for high school students, so that they can know about some technological teaching materials to gain an effective class, through searching on some scientific magazines to analyze why we should enforce these materials and promote the investigation in teachers in order to find out the technology trends to be taught in the classroom. technological teaching materials get on students motivation and interest to learn every topic that is introduced in the lesson. in this way, this work research shows the existed influence in teaching learning. in addition, some applications are showed to develop activities through applying these materials and reach the effectiveness of the lesson. the ending of this work is to affirm technological teaching materials look with favor on, easily, the learning of the english language.
Keywords: TEACHING-LEARNING; TEACHING MATERIAL; TECHNOLOGY; TEACHER; STUDENT